Goals of Public Procurement: A Fine Balancing Act for Malaysia - Cheong, May Fong (Journal of Malaysian and Comparative Law, 2011)
Public procurement is used to achieve various objectives which can be broadly termed as economic and non-economic (secondary or collateral). From an economic perspective, efficient procurement should ensure value for money (VFM). Further by virtue of the public element in the procurement, another main aim is the avoidance of abuse in the procurement process. These two core objectives of VFM and avoidance of abuse are achieved through principles of Competition and Transparency. Public procurement can also be used as a policy tool for social and industrial objectives as is the position in Malaysia. Where public procurement is used to accomplish redistributive and developmental goals, it can bear aims, methodology and effects that may be in conflict with, and compromise the other core objectives of VFM and abuse of process. In Malaysia, a fine balance needs to be struck to obtain the full benefits of Government Procurement.